Ealth Counseling About Early Detection of Breast Cancer with Breast Self Examination (Breast) In Adolescent Women - Sirait, Reni Aprinawaty (JURNAL PENGMAS KESTRA (JPK), 2023)
Breast cancer is a common disease in women and can cause death. The disease usually occurs in low- and middle-income countries, with most of the diagnoses being at an advanced studium. One effort that can be done in the context of early detection of breast cancer that can be done is breast self-examination (BSE). The purpose of this community service is to improve skills through BSE training. This activity will be held in Jati Sari Lubuk Pakam Village in April 2023. The target of this activity is 46 young women. The expected result of this community service activity is an increase in BSE skills which will be the basis for breast cancer prevention. The method used in this activity is the provision of material about breast cancer and BSE training. Based on the results of the activity, the respondents were very enthusiastic about participating in counseling activities and knowing more deeply about breast cancer prevention by self-breast examination (Sadari). Through this activity, it is hoped that young women will be able to apply knowledge about breast self-examination (BSE) regularly so that they can detect breast cancer early on.